2001
DOI: 10.1046/j.0022-202x.2001.01425.x
|View full text |Cite
|
Sign up to set email alerts
|

Change of Ultraviolet Absorbance of Sunscreens by Exposure to Solar-Simulated Radiation

Abstract: Regarding the outdoor behavior of the Caucasian population, modern sunscreens should provide high and broad-spectrum ultraviolet protection in the ultraviolet B as well as in the ultraviolet A range and should be photochemically stable for ultraviolet doses, which can be expected in solar radiation. At present an assessment of the photostability of suncare products is not a general requirement before marketing. In order to evaluate the photostability of suncare products we conducted an in vitro test and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
1
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 50 publications
(82 reference statements)
9
63
1
11
Order By: Relevance
“…We observed significant increases in transmittance for SPF 20 trials during a 2 hour period of exposure to the sun, but this phenomenon was not observed for SPF 40 trials (data not shown). Photo-inactivation of sunscreens may be responsible for the underestimation of UV-damage as described by Maier et al [28]. We have observed the advantages of repeated application of sunscreen during a period of 4 hours of solar radiation (data not shown).…”
Section: Discussionsupporting
confidence: 70%
“…We observed significant increases in transmittance for SPF 20 trials during a 2 hour period of exposure to the sun, but this phenomenon was not observed for SPF 40 trials (data not shown). Photo-inactivation of sunscreens may be responsible for the underestimation of UV-damage as described by Maier et al [28]. We have observed the advantages of repeated application of sunscreen during a period of 4 hours of solar radiation (data not shown).…”
Section: Discussionsupporting
confidence: 70%
“…1 (Gasparro, 2000). However, few photostable chromophores for broadband UVA filtering are available (Maier et al, 2001). Many UVA screens are inefficient, particularly in the near visible UVA and blue visible regions important for skin photosensitization, and rapidly undergo photoisomerization/ degradation due to uncontrolled excited state chemistry (Allen et al, 1996;Serpone et al, 2002).…”
mentioning
confidence: 99%
“…Estudos têm mostrado que alguns fotoprotetores perdem parte da sua proteção quando expostos à radiação UV (HAYWOOD et al, 2003;MAIER et al, 2001;MARROT et al, 2004;MAIER et al, 2005;SERPONE et al, 2002;TARRAS-WAHLBERG et al, 1999 Depois de selecionar a solução extratora mais adequada para os ensaios de fotoestabilidade, iniciou-se a padronização das condições cromatográficas para análise dos filtros solares, do trans-resveratrol e do beta-caroteno nas diferentes associações utilizadas nas formulações em estudo.…”
Section: Discussionunclassified
“…Estudos anteriores demonstram que alguns filtros solares perdem parte de sua capacidade fotoprotetora quando em contato com a radiação UV (DAMIANI et al, 2006;MARROT et al, 2004;GONZÁLEZ et al, 2007) e, ainda, que a fotoinativação não é um fenômeno que necessita de grandes doses de UV para acontecer (MAIER et al, 2001). Além disso, de acordo com Bonda, Zhang e Pavlovic (2011) o contato com a radiação UV pode reduzir significativamente a atividade antioxidante do trans-resveratrol.…”
Section: °Cunclassified
See 1 more Smart Citation